Preparations for pB11 tests in the FF-2B dense plasma focus - Lerner, Eric J.; Hassan, Syed M. (Frontiers in Physics, 2024)
The dense plasma focus (DPF) device has great potential as a fusion energy generator using hydrogenboron (pB11) fuel 1 . Experiments using deuterium have already demonstrated mean ion energies >200 keV, in the range needed for burning pB11 2 . To test that potential, we are preparing for experiments with hydrogen-boron fuel in the megampere DPF device, FF-2B. We plan to use isotopically-pure decaborane (B10H14) as the fuel source and have installed equipment for the safe handling and disposal of the toxic vapors from this material. High isotopic purity of the boron-11 is required to avoid generation of radioactive Be-7. While the main pB11 fusion reaction produces no neutrons, two side reactions do produce both neutrons and radioactive C-11. We show how these reaction products can be used with suitable detectors to provide accurate data on fusion yield, and the density and ion energy of the confined fusion-producing plasma.